A computer simulation designed for problem-based learning. - Rendas A; Pinto PR; Gamboa T (Medical Education, 1999)
OBJECTIVES: As problem-based learning is increasingly used in medical education, there is a growing need to capture the diversity of the events occurring during problem-based learning sessions in order to understand the way in which students learn. The computer simulation described attempts to analyse a posteriori how students reason and learn during such sessions. DESIGN: A computer simulation was designed to perform a detailed analysis of the following features: pattern of information searched, formulation of working hypothesis and identification of learning issues. The program, which has been running successfully for 2 years, was developed using local resources and accepts any clinical problem, provided it is written in a suitable text file format. The program has been applied in the discipline of pathophysiology. SETTING: Faculty of Medical Sciences of Lisbon, Portugal. SUBJECTS: Medical students. RESULTS: An example is presented of how prints were analysed in order to evaluate the 'progression profile' of the students, and a comparison is made with other similar instruments. CONCLUSIONS: The program improved understanding of the relationships between the inquiry strategy and hypothesis formulation and also of how self-learning (triggered by learning issues) influenced further analysis of the cases.